Highly cytotoxic substitutionally inert rhodium(III) tris(chelate) complexes: DNA binding modes and biological impact on human cancer cells - Hackenberg, Frauke; Oehninger, Luciano; Alborzinia, Hamed; Can, Suzan; Kitanovic, Igor; Geldmacher, Yvonne; Kokoschka, Malte; Wölfl, Stefan; Ott, Ingo; Sheldrick, William S. (Journal of inorganic biochemistry, 2011)
The antiproliferative properties and cellular impact of novel substitutionally inert rhodium(III) complexes of the types [Rh{(CH3)2 NCS2}2(pp)]Cl 3-5 (pp=5,6-Me2phen, dpq, dppz) and OC-6-23-[Rh(2-S-py)2(pp)]Cl 6 and 7 (2-S-py=pyridine-2-thiolate; pp=dpq, dppz) have been investigated for the adherent human cancer cell lines MCF-7 and HT-29 and for non-adherent Jurkat cells. Whereas CD and viscosity measurements indicate that the polypyridyl ligands of 4 and 5 intercalate into CT DNA, this is not the case for the analogous pyridine-2-thiolate complexes 6 and 7. Complexes 3-7 all exhibit a high antiproliferative activity towards MCF-7 and HT-29 cells, with IC50 values in the range 0.055-0.285μM. As established by online monitoring with a cell-based sensor chip, the highly cytostatic complex 6 (IC50=0.059 and 0.078μM) invokes an immediate concentration-dependent reduction of MCF-7 cell respiration and a time-delayed decrease in cellular impedance, which can be ascribed to the induction of cell death. Annexin V/PI assays demonstrated that 6 also has a pronounced antiproliferative activity towards Jurkat cells and that it invokes extensive apoptosis and high concentrations of reactive oxygen species in these leukemia cells. The observation of a dose-dependent inhibition of the oxygen consumption of isolated mice mitochondria indicates the involvement of an intrinsic mitochondrial pathway in this process.